A Linguistic Analysis of Identity, Emotion, And Gender in Best of Five Songs by Maroon 5 - Waldan, Bavari Muhammad; Juanda; Sari, Retno Purwani (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2025)
This study examines the language formulation of identity, emotion, and gender in five commercially and culturally significant songs by the American pop-rock band Maroon 5: "This Love," "She Will Be Loved," "Moves Like Jagger," "Sugar," and "One More Night." The study employs a qualitative descriptive approach based on stylistic analysis, metaphor theory, and gender discourse frameworks. The objective is to elucidate how language in popular music lyrics serves as a mechanism for shaping emotional expression and negotiating social identities. The findings indicate that identity is formed through personal pronouns, emotional contrasts, and metaphorical allusions, illustrating fluctuating roles of dominance and vulnerability. The Circumplex Model of Emotions (Troiano et al., 2022) analyzes emotional expression, uncovering patterns of high arousal, encompassing both positive (desire, lust) and negative (regret, heartbreak) emotions. Gender roles are depicted dynamically, fluctuating between conventional masculinity and emotionally expressive male identities. Lyrics like “Look into my eyes and I’ll own you” and “You pick up my broken pieces” illustrate both the reinforcement and transgression of patriarchal norms. The study presents two innovative conceptual contributions: emotional ambidexterity, the simultaneous presence of conflicting emotional states inside individual lyrical tales, and intra-discursive gender shifts, which characterize gender representation as fluid and multifaceted rather than static. These findings enhance the domains of language stylistics and popular culture studies by demonstrating how modern lyrics influence the formation of gendered and emotional identities inside the digital music environment. Keywords: Identity, Emotion, Gender